Scaling up agricultural carbon activities in Mbale Region, Uganda - Shames, Seth; Heiner, Krista; Kiguli, Lillian; Ssempala, Annet; Nantongo Kalunda, Pauline; Masiga, Moses (2015)
Agriculture is central to the economy of Uganda; it employs about 82% of the national workforce and is responsible for generating over 20% of Uganda’s GDP (Oling, Rwabizambuga, and Warren- rodriguez 2014). Over 800,000 smallholder farmers in the Mbale, Manafwa and Bududa Districts (Mbale region, total area 137,128 ha) depend on agriculture as their main source of livelihood (Mbogga 2013). Farmers in these districts mainly produce bananas and maize, which are consumed locally and exported to neighbor- ing countries like Kenya, as well as annual horticultural crops, such as carrots, Irish potatoes, onions, passion fruit and tomatoes. The Mbale region is also among the major coffee growing areas in Uganda, which is a major source of income for many farmers in the region. Additionally, most farmers also own livestock, which are usually kept in zero grazing systems or in combination with partial grazing (The Republic of Uganda 2013). However, the fertile land has also resulted in a high rate of pop- ulation growth and land fragmentation. The Mbale region has a high population density of about 1000 people per square kilome- ter, which means that the average size of land holding is small, between about 1 and 2 acres, forcing farmers to till the land intensively throughout the year (The Republic of Uganda 2013). In addition to making the soils less fertile and productive, these unsustainable farming practices also contribute to soil erosion. Furthermore, there has been significant forest degradation in the Mbale region (Banana et al. 2014). Because the region is moun- tainous, these unsustainable practices can easily lead to mud- slides when the soil is exposed to large amounts of rainfall. For these reasons, the Mt. Elgon region is one of the most vulnerable areas in Uganda to climate change, which was exemplified in the tragic landslide in Bududa and Manafwa Districts in March 2010 (Masiga 2013).